2018
DOI: 10.3389/fpsyt.2018.00216
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Features Associated With Autistic Traits in Obsessive-Compulsive Disorder

Abstract: Obsessive-compulsive disorder (OCD) is among the most debilitating psychiatric disorders. Comorbid autism spectrum disorder (ASD) or autistic traits may impair treatment response in OCD. To identify possible neurostructural deficits underlying autistic traits, we performed white matter tractography on diffusion tensor images (DTI) and assessed autistic trait severity using the Autism-Spectrum Quotient (AQ) in 33 OCD patients. Correlations between AQ and the DTI parameters, fractional anisotropy (FA), mean diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 74 publications
0
8
0
1
Order By: Relevance
“…Several studies [6,12,13,14,15,16,17,18,19,20] have been carried out using DTI to investigate the presence of abnormalities in the WM in individuals with ASD. [6] used DTI to compare the structure of the white matter of individuals with ASD to that of typically developed (TD) subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies [6,12,13,14,15,16,17,18,19,20] have been carried out using DTI to investigate the presence of abnormalities in the WM in individuals with ASD. [6] used DTI to compare the structure of the white matter of individuals with ASD to that of typically developed (TD) subjects.…”
Section: Introductionmentioning
confidence: 99%
“…They identified many confounds in the literature that could have affected the conclusions and highlighted the conflicting results. In [20], correlations between autism-spectrum quotient (AQ) and DTI parameters (FA, MD, AD, RD) were examined in white matter tracts that were altered in previous studies for obsessive-compulsive disorder (OCD) patients with ASD traits. Their results suggested that variations in WM features may be explained partially by autistic traits in OCD patients.…”
Section: Introductionmentioning
confidence: 99%
“…As repetitive behaviours are a common feature of both OCD and ASD, researchers have suggested a possible association between the two disorders (Bejerot 2001;Ivarsson 2008;Kushi 2019;Leyfer 2006;Mack 2010;Martin 2020;Russell 2005;Stewart 2016). For example, they might share common underlying causes, so that they might occur together in the same person more o en than would be expected (Kuno 2018;Liu 2019). Someone with ASD who also meets the criteria for OCD may face additional burdens, leading to more difficulties in everyday functioning (Martin 2020).…”
Section: Ocd and Asdmentioning
confidence: 99%
“…These are used for screening individuals with a high level of autistic and schizotypal traits. 28,29 The autistic traits measured by AQ that consisted of five dimensions: social skill, attention switching, attention to detail, communications, and imagination. 30 The schizotypal traits measured by SPQ included three dimensions: cognitive-perceptual, interpersonal, and disorganized.…”
Section: Introductionmentioning
confidence: 99%
“…The autism-spectrum quotient (AQ) and schizotypal personality questionnaire (SPQ) are the two most widely used psychometric self-report measures. These are used for screening individuals with a high level of autistic and schizotypal traits [ 28 , 29 ]. The autistic traits measured by AQ that consisted of five dimensions: social skill, attention switching, attention to detail, communications, and imagination [ 30 ].…”
Section: Introductionmentioning
confidence: 99%